Alumina Particles Are Snowballing with Propylene Oxide–Synthesis of Alumina Aerogels with Free Adjustable Particle and Pore Sizes. Issue 5 (29th April 2016) - Ren, Lili; Li, Xueai; He, He
Abstract: Abstract : Porous materials have widely application like adsorption, separation, catalysis, thermal insulation, etc., but how to prepare a kind of porous material with the specific particle and pore sizes according to the actual needs is always a tough problem. Although many studies have been involved in the regulation of the particle and channel sizes, until now the report clearly accessed to continuously adjustable particle and pore sizes is still very little. Here we demonstrate a simple method to prepare alumina aerogels with the required particle and pore size, which do not need to use any other complex structural directing materials, and can be easily achieved only by changing the amount of propylene oxide. This method realizes the controllable synthesis in real sense, which is helpful to promote the practical application of alumina aerogels, and also has a promising application in controllable synthesis of other porous materials. Abstract : The particle and pore size of the alumina aerogels can be freely controlled by controlling the amount of propylene oxide, and the whole process is like a particle in a snowball. With the growth of the particle, the alumina aerogel showed different reaction process and surface gloss. This preparation method, without using complex structural directing materials, simple and easy to operate, can be applied to the preparation of other porous materials.